Future insights into enterprise risk management, competitive advantage, and firm performance - Lawati, Ammar Al; Hussin, Baharuddin M; Kadir, Mohd Rizuan Abdul; Khudari, Mohamed (Edelweiss Applied Science and Technology, 2025)
Enterprise Risk Management (ERM) has emerged as a key aspect of the academic and professional spheres. Although it is gradually recognized as having potential benefits, there is still a significant gap related to the exact relationship between ERM and firm performance. Ongoing research endeavors to fill this void by exploring the influence of ERM and aligning its dimensions with the concept of competitive advantage. This study presents a comprehensive overview of ERM, utilizing the resource-based view (RBV) and contingency theories as a lens to examine its effects on performance, with competitive advantage serving as a mediating factor. This study extends the current literature by introducing new findings and examining the relationship between strategy and ERM. The results of this research not only explain the key aspects of ERM and its effects on firm performance but also offer real-world guidance. These insights could serve as a guide to bridge the gap between what managers expect to result from ERM and what is implemented to create competitive advantage strategies. This investigation aims to contribute to the literature on the role of ERM in corporate strategy and provide practical guidelines for incorporating ERM into organizations.